INDIGENOUS POLICIES, MULTICULTURALISM AND ‘URBAN INDIGENOUS STATE APPROACH’ - Antileo Baeza, Enrique (Revista de Historia Social y de las Mentalidades, 2014)
Interest in urban reality of indigenous people  –particularly in Mapuche society and its great  population living in Santiago-can be understood  as a recent change over the indigenous  policies in Chile, that is to say, as part of the  transformation in speeches and practices after  the dictatorship and also as part of what we  might call the generation of a ‘state indigenous  engineering’. That engineering in the beginning  had a strong emphasis on rural aspects and  strategies, but nowadays the emphasis is upon  new trials along indigenous state agencies, new  windings and new strategies where the visibility  of urban settlement (Census 1992, Census 2002,  Casen 2006, Casen 2009) has been a key on  ownership of the problem and the springing up  of specific plans and programs for the sector.  In this article we propose a brief overview of  indigenous policies, and then we will deploy  a critical analysis of multiculturalism in Chile  within Latin American reality. Starting from  the previously mentioned, we will also discuss  some proposals to indigenous residents of cities,  summed up in what we call ‘urban indigenous  state approach’.
Keywords: Indigenous policies; Urban indigenous state approach; Multiculturalism; Colonialism